Information literacy in on-line learning: A distance tutoring course study - Conde, César Augusto Galvão Fernandes; da Cruz, Dalila Gimenes; Bartalo, Linete [UNESP] (My University, 2018)
It is necessary to investigate the information competences in order to face one of the main challenges of contemporary education: to design continuing education programs, centered on the student and that contribute to the expansion of information skills as a fundamental condition for the effectiveness of learning. In distance education (EaD) the autonomy to learn is fundamental and the information skills contribute to a greater capacity for reflection, access, evaluation and use of the information for the structuring of new knowledge. There is a long way to go in the EAD mode, as people need to learn how to deal more effectively with the large number of information available and mediated by the use of information technologies. The objective of this study was to analyze the information skills of students of the Distance Learning course in relation to access, evaluation and use of information for learning. The survey counted on 113 participants of the 5th class of the course, offered in the online modality by the Nucleus of Distance Education of the State University of Londrina. For the data collection, a questionnaire was applied on a Likert scale. The results, expressed as averages, measured the frequency of students’ behaviors in relation to access, evaluation and use of information for learning and showed a propensity to consult in digital sources. The study can contribute to the reflection on the themes related to distance education and the understanding of the influence of information skills for the greatest success in the use of online learning.
Alfabetización informacional en el aprendizaje en línea: Estudio en un curso de tutoría a distancia
Competência em informação na aprendizagem on-line: Estudo em um curso de tutoria a distância
Keywords: Distance learning; E-learning; Information behavior; Information competency